PERANCANGAN AWAL INTERIOR YAYASAN RUMAH PAGI BAHAGIA DI BINTARO - Adi Ismanto; Michella Angelina; Canisha Chrystella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Education is the foundation and driving force for the progress of a nation. Indonesia, as a developing country is still looking for a quality education system to produce the best and reliable human resources. Formal education must also be equipped with other supporting education in order to be able to achieve the vision of the country, namely